A genome-wide association study identifies new loci associated with response to SARS-CoV-2 mRNA-1273 vaccine in a cohort of healthy healthcare workers - Cabrera-Serrano, Antonio José; Ruiz-Durán, Lucía; Gutiérrez-Bautista, Juan Francisco; Carretero-Fernández, María; ter Horst, Rob; Li, Yang; Reyes-Zurita, Fernando Jesús; García-Verdejo, Francisco José; Netea, Mihai G.; Sánchez-Rovira, Pedro; López-Nevot, Miguel Ángel; Sampedro, Antonio; et al. (Frontiers in Immunology, 2025)
IntroductionThe COVID-19 pandemic had significant global public health consequences, affecting over 200 countries and regions by 2020. The development and efficacy of specific vaccines, such as the mRNA-1273 (Spikevax®) vaccine developed by Moderna Inc., have substantially reduced the impact of the pandemic and mitigated its consequences. This study aims to identify novel genetic loci associated with the effectiveness of the mRNA-1273 vaccine, as measured by elevated anti-Spike (anti-S) IgG levels at multiple time points post-vaccination.Materials and methodsWe conducted three genome-wide association studies (GWAS) in a cohort of Spanish healthcare workers, analyzing anti-S IgG levels at one-month post-vaccination (n=567), at three months post-vaccination (n=447), and the difference in circulating anti-S IgG levels between these two time points (n=447).ResultsWe identified fourteen novel loci associated with increasing concentrations of anti-S IgG post-vaccination (p=5.01×10-13 and p=2.81×10-8). Functional results showed that some of the novel risk alleles influence the absolute counts of specific B cell subsets (p=2.57×10-5-8.82×10-3), which are involved in immune signaling pathways and metabolic processes. Furthermore, these variants co-localize with multiple QTLs and epigenetic marks, suggesting that the GWAS hits may affect regulatory activity in promoters, enhancers, and transcriptional regions, thereby modulating gene expression relevant to the humoral immune response.DiscussionIn conclusion, this study highlights the complex interplay of genetic factors influencing the immune response to vaccination, particularly through modulation of B cell activity, immune signaling pathways, and metabolic processes. The identification of genetic variants could inform future strategies to enhance vaccine efficacy and provide a deeper understanding of individual variability in vaccine responses, especially for COVID-19 and other viral infections.